Dead-end membrane distillation with localized interfacial heating for sustainable and energy-efficient desalination. (1st February 2021) - Mustakeem, Mustakeem; Qamar, Adnan; Alpatova, Alla; Ghaffour, Noreddine
Highlights: Localized heating of feed water using inbuilt heating element in MD is proposed. Novel dead-end MD-intermittent flush system is most efficient. 133% increase in water vapor production is achieved. GOR increased by 132% and SEC decreased by 57%. SEC of new concept approaches theoretical thermodynamic limit for water evaporation. Abstract: Membrane distillation (MD) has the high potential to circumvent conventional desalination limitations in treating highly saline brines. However, the performance of MD is limited by its low thermal efficiencyand temperature polarization (TP) effect. Consequently, the driving force decreases when heat loss increases.In this study, we propose to minimize TP through localized heating where the thin feed channel was heated uniformly at the membrane-liquid interface without changing the properties of the membrane.This concept was further improved by implementing a new dead-end MD configuration. Investigated for the first time, this configuration eliminated circulation heat losses, which cannot be realized in conventional MD due to a rapid temperature stratification. In addition, the accumulation of foulants on the membrane surface was successfully controlled by intermittent flushing. 3-Dimensional conjugate heat transfer modeling revealedmore uniform heat transfer and temperature gradient across the membrane due to the increased feed water temperature over a larger membrane area. The increase of water vapor flux (45%) and the reduction of heat lossobserved in the new dead-end concept led to a decrease of the specific energy consumption by 57%, corresponding to a gain output ratio increase of about 132 %, compared to a conventional bulk heating, while preserving membrane integrity. A conjugate heat transfer model was deployed in ANSYS-Fluent framework to elucidate on the mechanism of flux enhancement associated with the proposed technique. This study provides a framework for future sustainable MD developmentby maintaining a stable vapor flux while minimizing energy consumption. Graphical abstract: Image, graphical abstract